ответ:
\frac{13k-4}{3-13k}+ \frac{x}{3-13k}=1
\frac{13k-4+x}{3-13k}= \frac{3-13k}{3-13k}
\frac{13k-4+x}{3-13k}- \frac{3-13k}{3-13k} =0
\frac{13k-4+x-(3-13k)}{3-13k}=0
\frac{13k-4+x-3+13k}{3-13k}=0
\frac{26k-7+x}{3-13k}=0
\left \{ {{26k-7+x=0} \atop {3-13k \neq 0}} \right. ; \left \{ {{x=-26k+7} \atop {k \neq \frac{3}{13} }} \right. ; \left \{ {{x=7-26k} \atop {k \neq \frac{3}{13} }} \right.
ответ: если k \neq \frac{3}{13} , то x=7-26k
объяснение:
cos105' cos5'+sin105' sin5'/ cos18' cos62'-sin 62' cos72' =
=cos(105 -5) / cos18 cos62 - sin 62 cos(90 - 18) =
=cos100 /cos18' cos62 - sin 62 sin18 =
=cos100 /cos(62 + 18) =
=cos100 /cos80 =
=cos(90 +10) /cos(90-10) =
=-sin10 /sin10 =-1